URGENSI LITERASI DIGITAL KEAGAMAAN DALAM PENDIDIKAN AGAMA ISLAM DI ERA POST-TRUTH: SYSTEMATIC LITERATURE REVIEW - Zulvann Zahra; Koderi Koderi; Fitriani Fitriani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The rapid advancement of digital technology has transformed how people access religious information, while the post-truth era has intensified challenges through the widespread dissemination of misinformation, disinformation, and emotionally driven narratives that may influence students’ religious understanding. This situation highlights the importance of religious digital literacy as an essential competency in Islamic Religious Education (IRE). This study aims to analyze the urgency of religious digital literacy in IRE within the post-truth era using a Systematic Literature Review (SLR) approach. Data were collected from Scopus-indexed publications retrieved through the Scopus database and Publish or Perish, covering the 2020–2025 publication period. The literature selection followed the PRISMA guidelines with the support of Covidence software. Of the 148 identified articles, 16 met the inclusion criteria and were analyzed comprehensively. The findings reveal that religious digital literacy in IRE encompasses critical thinking, digital media ethics, awareness of social influences, and the ability to filter and verify religious information. The review also identifies several major challenges, including limited information verification skills, inadequate digital competence among educators, the dominance of emotional approaches in receiving religious information, and the suboptimal integration of religious digital literacy into the IRE curriculum. The study concludes that strengthening religious digital literacy plays a strategic role in fostering students who are critical, responsible, tolerant, and capable of applying the principle of tabayyun when responding to religious information in the post-truth era. ABSTRAK Perkembangan teknologi digital telah mengubah pola masyarakat dalam mengakses informasi keagamaan, sementara era post-truth menghadirkan tantangan berupa meningkatnya penyebaran hoaks, disinformasi, dan dominasi narasi emosional yang berpotensi memengaruhi pemahaman keagamaan peserta didik. Kondisi ini menjadikan literasi digital keagamaan sebagai kompetensi penting dalam pembelajaran Pendidikan Agama Islam (PAI). Penelitian ini bertujuan menganalisis urgensi literasi digital keagamaan dalam PAI di era post-truth melalui pendekatan Systematic Literature Review (SLR). Data diperoleh dari artikel yang terindeks Scopus dan ditelusuri menggunakan database Scopus serta Publish or Perish pada rentang publikasi tahun 2020–2025. Seleksi literatur dilakukan berdasarkan pedoman PRISMA dengan bantuan perangkat lunak Covidence. Dari 148 artikel yang teridentifikasi, sebanyak 16 artikel memenuhi kriteria inklusi dan dianalisis secara mendalam. Hasil penelitian menunjukkan bahwa literasi digital keagamaan dalam PAI mencakup kemampuan berpikir kritis, etika bermedia digital, kesadaran terhadap pengaruh sosial, serta kemampuan menyaring dan memverifikasi informasi keagamaan. Penelitian juga mengidentifikasi tantangan berupa rendahnya kemampuan verifikasi informasi, keterbatasan kompetensi digital pendidik, dominasi pendekatan emosional dalam menerima informasi agama, serta belum optimalnya integrasi literasi digital keagamaan ke dalam kurikulum PAI. Disimpulkan bahwa penguatan literasi digital keagamaan berperan strategis dalam membentuk peserta didik yang kritis, bertanggung jawab, toleran, dan mampu menerapkan prinsip tabayyun dalam menyikapi informasi keagamaan di era post-truth.